Generalized Strong Commutativity Preserving Centralizers of Semiprime Î“- Rings - Hamil, Shahed Ali; Majeed, Abdulrahman H. (Iraqi Journal of Science, 2019)
In this paper, we introduce the concept of generalized strong commutativity (Cocommutativity) preserving right centralizers on a subset of a Î“-ring. And we generalize some results of a classical ring to a gamma ring.